Thrift and thriving in America capitalism and moral order from the Puritans to the present - Yates, Joshua J.; Hunter, James Davison, 1955- (New York ; Oxford : Oxford University Press, 2011)
'Thrift and Thriving in America' is a collection of essays from scholars across the humanities and social sciences on the seminal importance of thrift to American culture and history.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Saving and investment -- Moral and ethical aspects -- United States -- History; Thriftiness -- United States -- History; Capitalism -- United States -- History